2013
DOI: 10.1097/aog.0b013e3182a1ba56
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Gefitinib, an Epidermal Growth Factor Receptor Inhibitor, on Human Placental Cell Growth

Abstract: Combining gefitinib with methotrexate potently inhibits placental cell growth in vitro and in mouse models. The combination may have potential in treating ectopic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…We have demonstrated effective management of women with non-tubal EPs and pretreatment hCGs as high as 48 558 IU/l by combining minimal doses of methotrexate with a short course of gefitinib. This co-treatment approach can achieve better treatment outcomes with lower overall drug exposure (Nilsson et al , 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated effective management of women with non-tubal EPs and pretreatment hCGs as high as 48 558 IU/l by combining minimal doses of methotrexate with a short course of gefitinib. This co-treatment approach can achieve better treatment outcomes with lower overall drug exposure (Nilsson et al , 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we obtained preliminary data suggesting this combination may have a time to resolution which is 34% faster compared with treatment using methotrexate alone (Nilsson et al , 2013; Skubisz et al , 2013). This suggested adding gefitinib to methotrexate may improve on its efficacy in medically resolving ectopic pregnancies.…”
Section: Introductionmentioning
confidence: 91%
“…However, we believe our preliminary observations on potential efficacy are considerably strengthened when considered together with our preclinical data. 14 We have generated laboratory data, both in vitro and in animal models, suggesting adding gefitinib to methotrexate enhances its ability to induce placental cell death. Therefore, the possibility that gefitinib may enhance the ability of methotrexate to resolve ectopic pregnancy is biologically plausible.…”
Section: Discussionmentioning
confidence: 99%
“…It has good oral bioavailability and often causes transient diarrhea and skin rash. 12,13 In preclinical studies, 14 we have found gefitinib supra-additively augments methotrexate-induced regression of placental tissue. Given the encouraging results obtained from the preclinical studies, 14 we translated our finding to humans, conducting a phase I trial to assess the safety, tolerability, and efficacy of combination gefitinib (once-daily 250 mg oral gefitinib taken up to 7 days) and intramuscular methotrexate to treat ectopic pregnancy.…”
Section: Level Of Evidence: IImentioning
confidence: 94%
“…In preclinical studies, we found that EP implantation sites express high levels of EGFR and that gefitinib augments MTX-induced regression of pregnancy-like tissue 8. To translate this into clinical care, we performed a phase I single-arm open-label dose-escalation study administering a combination of 250 mg oral gefitinib (one dose (n=3), three daily doses (n=3), seven daily doses (n=6)) and intramuscular MTX (50 mg/m 2 ) to 12 women with tEPs 9.…”
Section: Introductionmentioning
confidence: 99%